Skeletal Muscle Microvascular Dysfunction Manifests Early in Diabetic Cardiomyopathy - Loai, Sadi; Zhou, Yu-Qing; Vollett, Kyle D. W.; Cheng, Hai-Ling Margaret (Frontiers in Cardiovascular Medicine, 2021)
Aim: To perform a deep cardiac phenotyping of type II diabetes in a rat model, with the goal of gaining new insight into the temporality of microvascular dysfunction, cardiac dysfunction, and exercise intolerance at different stages of diabetes. Methods and Results: Diabetes was reproduced using a non-obese, diet-based, low-dose streptozotocin model in male rats (29 diabetic, 11 control). Time-course monitoring over 10 months was performed using echocardiography, treadmill exercise, photoacoustic perfusion imaging in myocardial and leg skeletal muscle, flow-mediated dilation, blood panel, and histology. Diabetic rats maintained a normal weight throughout. At early times (4 months), a non-significant reduction (30%) emerged in skeletal muscle perfusion and in exercise tolerance. At the same time, diabetic rats had a normal, slightly lower ejection fraction (63% vs 71% control, p < 0.01), grade 1 diastolic dysfunction (E/A=1.1 vs 1.5, isovolumetric relaxation time=34 ms vs 27 ms; p < 0.01), mild systolic dysfunction (ejection time=69 ms vs 57 ms, isovolumetric contraction time=21 ms vs 17 ms; p < 0.01), and slightly enlarged left ventricle (8.3 mm vs 7.6 mm diastole; p < 0.01). Diastolic dysfunction entered grade 3 at Month 8 (E/A=1.7 vs 1.3, p < 0.05). Exercise tolerance remained low in diabetic rats, with running distance declining by 60%; in contrast, control rats ran 60% farther by Month 5 (p < 0.05) and always remained above baseline. Leg muscle perfusion remained low in diabetic rats, becoming significantly lower than control by Month 10 (33% SO2 vs 57% SO2, p < 0.01). Myocardial perfusion remained normal. Femoral arterial reactivity was normal, but baseline velocity was 25% lower than control (p < 0.05). High blood pressure appeared late (8 months). Histology confirmed absence of interstitial fibrosis, cardiomyocyte hypertrophy, and microvascular rarefaction in the diabetic heart. Rarefaction was also absent in leg skeletal muscle. Conclusion: Diabetic rats exhibited exercise intolerance and cardiac dysfunction, in which some changes related to heart failure with preserved ejection fraction were seen. Importantly, alongside exercise intolerance and early cardiac changes was the early emergence of reduced skeletal muscle perfusion from microvessel constriction. Hypertension appeared late after muscle vasoconstriction had advanced significantly.